Plasma-made silicon nanograss and related nanostructures - Shieh, Jiann; Ravipati, Srikanth; Ko, Fu-Hsiang; Ostrikov, Kostya (Ken) (My University, 2011)
Plasma-made nanostructures show outstanding potential for applications in nanotechnology. This paper provides a concise overview on the progress of plasma-based synthesis and applications of silicon nanograss and related nanostructures. The materials described here include black silicon, Si nanotips produced using a self-masking technique as well as self-organized silicon nanocones and nanograss. The distinctive features of the Si nanograss, two-tier hierarchical and tilted nanograss structures are discussed. Specific applications based on the unique features of the silicon nanograss are also presented.